2015
DOI: 10.3233/ves-150556
|View full text |Cite
|
Sign up to set email alerts
|

Variables associated with outcome in patients with bilateral vestibular hypofunction: Preliminary study

Abstract: Consideration of baseline factors may provide guidance for setting patient goals. Further research is needed determine what factors predict outcome and to develop more effective treatment strategies for those patients who do not improve.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(66 citation statements)
references
References 0 publications
3
62
0
1
Order By: Relevance
“…There are now several commercially available, video-based systems (most head-mounted, one wall-mounted) [9193], with which a clinician can measure the VOR from each of the six canals in a reasonably co-operative adult or child [94, 95] in about 10 min. Audiologists [96] and physiotherapists [97] are already doing so. Here, we consider four common clinical situations in which the video head impulse test (vHIT) can help with diagnosis.…”
Section: Video Head Impulse Testingmentioning
confidence: 99%
“…There are now several commercially available, video-based systems (most head-mounted, one wall-mounted) [9193], with which a clinician can measure the VOR from each of the six canals in a reasonably co-operative adult or child [94, 95] in about 10 min. Audiologists [96] and physiotherapists [97] are already doing so. Here, we consider four common clinical situations in which the video head impulse test (vHIT) can help with diagnosis.…”
Section: Video Head Impulse Testingmentioning
confidence: 99%
“…Patients with BVH are at higher risk for falls compared to those with UVH. 22 Approximately 35–50% of BVH patients have a history of falls. 2,23 BVH patients may be refractory to the benefits of vestibular rehabilitation.…”
Section: Discussionmentioning
confidence: 99%
“…Symptoms of BVD include oscillopsia, vertigo, headaches, nystagmus and chronic imbalance [2]. These are attributable to severely reduced or absent function of vestibular nerves, end organs or both [9]. Diminished function of the vestibular system adversely affects the VOR and postural-righting reflexes, which reduces ability to balance in both static and dynamic situations.…”
Section: Vestibular Dysfunctionmentioning
confidence: 99%
“…BVD has an adverse effect on quality of life; 84% of patients reported a significant decrease in their quality of life and one study reported a 31-fold increase in the risk of falls [9]. Patients commonly quote a lack of independence, inability to drive and the need for assistance with daily activities as prevalent negative factors [10].…”
Section: Vestibular Dysfunctionmentioning
confidence: 99%
See 1 more Smart Citation